Is news engagement worthwhile?: Studying young audiences’ engagement with YouTuber-like news content - Himma-Kadakas Marju; Ferrer-Conill Raul (Nordicom Review, 2022)
While traditional media often fails to engage young audiences with news, YouTubers’ content gains popularity and attracts attention with specific stylistic practices. Based on dimensions of audience engagement and a worthwhileness approach, this article examines how young audiences engage with YouTubers’ formats and genres used in news media products. Findings of five focus group interviews with Estonian teenagers show that while specific dimensions of engagement may increase due to a more relatable format, interest in traditional news content remains limited regardless of repackaging to a YouTube-intrinsic production. This article contributes to audience studies by demonstrating to news organisations that trying to engage younger audiences through mere formatting while forgetting content might not be worthwhile. However, making news more entertaining and adopting the youth's interpretation of what news is could prime young audiences to consume news through social media.